2006
DOI: 10.1007/s10751-006-9452-9
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer and optical investigation of Co3−x Fe x O4 thin films grown by sol–gel process

Abstract: Structural transformation and the related variation in magnetic and optical properties of Co 3−x Fe x O 4 thin films grown by a sol-gel method have been investigated as the Fe composition varies up to x=2. The normal spinel phase is dominant below x=0.55 and the inverse spinel phase grows as x increases further. Conversion electron Mössbauer spectroscopy (CEMS) measurements indicate that the normal spinel phase have octahedral Fe 3+ ions mostly while the inverse spinel phase contain octahedral Fe 2+ and tetrah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
3
4
0
Order By: Relevance
“…Sales et al [23] investigating powders with the composition 3(Al 1.95 Co 0.025-Ti 0.025 O 3 )$2SiO 2 , heat treated at 995 C for 1 h, found peaks at 510 nm, 575 nm and 618 nm. The position of the bands I, II and III in the present paper, 550, 580 and 620 nm, generally agrees with the values disclosed in the literature [22,24].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Sales et al [23] investigating powders with the composition 3(Al 1.95 Co 0.025-Ti 0.025 O 3 )$2SiO 2 , heat treated at 995 C for 1 h, found peaks at 510 nm, 575 nm and 618 nm. The position of the bands I, II and III in the present paper, 550, 580 and 620 nm, generally agrees with the values disclosed in the literature [22,24].…”
Section: Resultssupporting
confidence: 93%
“…Kim et al [24] studied the Co 3Àx Fe x O 4 system and reported three visible peaks at 1.65 eV (752 nm), 2.4 eV (517 nm) and 2.8 eV (443 nm). The first peak was assigned to a t 2g (Co 3þ ) / t 2 (Co 2þ ) dd charge transfer (CT) transition, from the d(t 2g ) states of the octahedral Co 3þ ion to the d(t 2 ) states of the tetrahedral Co 2þ ion.…”
Section: Resultsmentioning
confidence: 99%
“…The additional hematite phase in chemical routed Co 3x Fe 3(1Àx) O 4 samples was also reported for low Co content [17,21]. This is due to doping effects of Co ions in Fe 3 [24,26]. This structural transformation from inverse spinel (for low Co content) to normal spinel (for high Co content) is consistent to the results of Mössbauer spectroscopy [24] and FTIR spectroscopy [19].…”
Section: Sample Preparation and Characterizationsupporting
confidence: 80%
“…This is due to doping effects of Co ions in Fe 3 [24,26]. This structural transformation from inverse spinel (for low Co content) to normal spinel (for high Co content) is consistent to the results of Mössbauer spectroscopy [24] and FTIR spectroscopy [19]. Room temperature magnetic properties in low field regime (field up to ±16 kOe) were studied using VSM (Lakeshore 7404, USA).…”
Section: Sample Preparation and Characterizationsupporting
confidence: 79%
“…CoCr 2 O 4 and Co 3 O 4 are normal cubic spinels usually synthesized by solid state reaction for application in the pigment production [1,2]. Oxides and chromites have also been reported as active materials in catalysis, magnetic compounds and substrates for thin film growth [3][4][5][6][7][8][9]. The variety of oxidation states, the different host lattices in which chromium or cobalt can be found and the variety of synthesis routes explain both the color versatility and the different properties associated with these cations.…”
Section: Introductionmentioning
confidence: 99%